How Government Information Release Affect Stock Market during Dramatic Public Health Shocks? The Intermediating Role of Public Sentiment - Zhao, Sijia; Liu, Ying; Lv, Benfu; Shangguan, Zijian (International Journal of Economics and Financial Issues, 2022)
During dramatic public health shocks, the impact of anti-epidemic policies on public sentiment is uncertain, and public sentiment has a significant impact on the stock market. But the relationship between the three is not clear. This paper uses government information release to reflect anti-epidemic policies, uses personal weibo to calculate public sentiment, and analyzes the relationship between Government information release, public sentiment and stock market. Through the Bi-LSTM classification model analysis about 200,000 microblog data during COVID-19, and build panel data regression model. The results show that: public sentiment have a significant positive impact on stock returns; Government information release have a significant positive impact on public sentiment; public sentiment play a intermediating role between government information release and stock market; Influenced by the enterprise size and the industry it belongs to, there is heterogeneity in public sentiment’s impact.